Dendrosomal nanocurcumin prevents EBV-associated cell transformation by targeting the lytic cycle genes of the Epstein-Barr virus in the generation of lymphoblastoid cell line - Mahboobeh Cheragh; Majid Sadeghizadeh; Mohammad Hasan Pouriayevali; Masoud Parsania (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Targeting the lytic cycle of the Epstein-Barr virus (EBV) has been considered a new treatment strategy for malignancies caused by this virus.  This study aimed to investigate the effect of Dendrosomal NanoCurcumin (DNC) to prevent cell transformation and inhibit the expression of viral lytic gene expression in the generation of lymphoblastoid cell line (LCL).Materials and Methods: Cell viability of LCLs and PBMCs was performed by MTT assay, and flow cytometry (Annexin/PI) was used for evaluation of apoptosis. CD markers on the surface of generated LCL (CD19) cells were examined for cell validation. The effect of DNC on transformation was evaluated by examining cell morphology and determining the expression level of lytic genes BZLF1, Zta, BHRF1, and BRLF1 of EBV using Real-time PCR. Student’s t-test was used for statistical analysis.Results: The MTT assay showed that DNC can inhibit the proliferation of LCL in a dose-dependent manner. The 50% cytotoxic concentration (CC50) of DNC and curcumin for LCL was determined 38.8 µg/ml and 75 µg/ml, respectively after 72 hr. Also, Real-time PCR data analysis showed that DNC in 30 µg/ml concentration significantly inhibited cell transformation in the LCL and significantly reduced viral lytic genes such as BZLF1, Zta, BHRF1, and BRLF1expression compared to control.Conclusion: Overall, these findings show that DNC reduces the expression of the viral lytic cycle genes and also the induction of cell apoptosis and finally prevents the generation of LCL.